Perception and Motivation of Students on EFL Learning Through Instagram - Ahmad Saputra; Qamariah, Zaitun; Imam Qalyubi (DIAJAR: Jurnal Pendidikan dan Pembelajaran, 2023)
Globalization is emerging in a digital era, making it easier to access information, share, and exchange things via social networks, such as Instagram. The purpose of this study is to analyze students’ perceptions of Instagram as a platform to motivate EFL learners. The researcher assumes Instagram is an easy platform and can be used to learn English anywhere and anytime without time restrictions. The research was conducted on the students of IAIN Palangka Raya. Researchers used quantitative methods to solve research problems and employ questionnaires and interviews as data-gathering instruments in this study. For the English Study Programs at IAIN Palangka Raya, a research sample was chosen by purposive sampling in which the sample should be the third-semester students who were also active users of Instagram and active followers of accounts that teach English. This study found that 76% of TEFL students are motivated to learn English using Instagram due to its attractive and easy-to-use application design, fun activities, and improved English vocabulary, writing, speaking, and listening skills.